PEDAGOGICAL INNOVATION STUDIES AS AN INTERDISCIPLINARY FIELD OF PROFESSIONAL PEDAGOGICS - Kozak, Lyudmyla (Continuing Professional Education: Theory and Practice, 2019)
The paper presents a theoretical and methodological analysis of pedagogical innovation studies as an interdisciplinary field of professional pedagogics; defined is the meaning of pedagogical innovation studies in the development of theoretical and practical principles of innovative processes in education; determined are the object, subject and the objectives of pedagogical innovation studies; conducted is the definitional analysis of the following concepts: «innovation studies», «pedagogical innovation studies», «interdisciplinary research», «innovation», «educational innovation», «innovative educational process», «innovative pedagogical activity», «professional pedagogics»; it is established that in the broad sense pedagogical innovation studies are considered as a new interdisciplinary scientific field that studies topical and significant phenomena and facts in conjunction with the philosophical, psychological, social, cybernetic and pedagogical approaches with a purpose to realize the unique features of the educational space and to establish the universal laws and regularities, and in the narrow sense, as a branch of research aimed at mastering of innovative processes in education; the specificity of innovation is that it is an interdisciplinary methodology of a special type, which provides an integration of knowledge, during which special sciences (economic and managerial, sociology, psychology and cybernetics) retain their autonomy and specificity, but their theoretical concepts and factual data are joined together around the methods of research of innovation and innovation activity problems, integrating diverse scientific knowledge to improve their practical effectiveness; defined isthe content of the «Pedagfogical Innovation Studies» curriculum, aimed at the development of future teacher’s competence in the field of innovative professional activity; defined are the purpose, objectives, structure and content-related component of the curriculum as well as forms and methods of its implementation; proven is a positive influence of pedagogical innovation on forming of educationists’ capacity for innovative professional activity.